Synthesis of an Immunologically Active Heptamannoside of Mycobacterium tuberculosis by the [Au]/[Ag]-Catalyzed Activation of Ethynylcyclohexyl Glycosyl Carbonate Donor - Shinde, Ganesh P. (American Chemical Society, 2025)
Tuberculosis (TB) is one of the most dreadful diseases, killing more than 3 million humans annually. M. tuberculosis (MTb) is the causative agent for TB and has a thick and waxy cell wall, making it an attractive target for immunological studies. In this study, a heptamannopyranoside containing 1 → 2 and 1 → 6 α-mannopyranosidic linkages has been explored for the immunological evaluations. The conjugation-ready heptamannopyranoside was synthesized by exploiting the salient features of recently discovered [Au]/[Ag]-glycosidation of ethynylcyclohexyl glycosyl carbonate donors. The glycan was conjugated to the ESAT6, an early secreted protein of MTb for further characterization as a potential subunit vaccine candidate. © 2024 American Chemical Society.